Prescribing and regulating exercise with RPE after heart transplant: a pilot study - Ciolac, Emmanuel Gomes [UNESP]; Castro, Rafael Ertner [UNESP]; D'Andrea Greve, Julia Maria; Bacal, Fernando; Bocchi, Edimar Alcides; Guimaraes, Guilherme Veiga (Lippincott Williams &wilkins, 2015)
Purpose The objective of this study is to analyze the use of the 6-20 RPE scale for prescribing and self-regulating heated water-based exercise (HEx) and land-based exercise (LEx) in heart transplant recipients.Methods Fifteen (five females) clinically stable heart transplant recipients (time since surgery = 4.0 2.5 yr) age 46.7 11.8 yr underwent a symptom-limited maximal graded exercise test on a treadmill to determine their HR at anaerobic threshold (HRAT), respiratory compensation point (HRRCP), and maximal effort (HRmax). After a week, patients were randomized to perform 30 min of both HEx (walking inside the pool) and LEx (treadmill walking) sessions at a pace between 11 and 13 on the 6-20 RPE scale and had their HR measured every 4 min. The interval between sessions was 48-72 h.Results No significant differences between sessions were found in the average HR during HEx and LEx. Patients showed a delay in HR increase during both interventions, with the stabilization beginning after 8 min of exercise. Exercise HR was maintained between the HRAT and HRRCP (in the aerobic exercise training zone) for the most part of both HEx (72% of HR measurements) and LEx (66% of HR measurements). Only a few HR measurements stayed below HRAT (HEx = 9%, LEx = 13%) or above HRRCP (HEx = 19%, LEx = 21%) during both exercise sessions.Conclusion Exercise HR was maintained in the aerobic exercise training zone (between HRAT and HRRCP) for the most part of both sessions, suggesting that the 6-20 RPE scale may be an efficient tool for prescribing and self-regulating HEx and LEx in heart transplant recipients.
Keywords: Aerobic exercise; Cardiac denervation; Heart rate; Heart transplantation; Rating of perceived exertion; Rehabilitation